Disaster risk financing and insurance for earthquake-prone state buildings in Indonesia - Marlina, Hesti; Ruslanjari, Dina; Hakim, Inayah B.A. (Jamba, 2024)
Indonesia situated within the volatile Ring of Fire, faces recurring and devastating earthquakes that pose significant economic threats. The Government of Indonesia (GoI) has initiated a disaster risk financing strategy to address these challenges. However, the implementation of disaster insurance within this strategy remains limited. This study examined the GoI's disaster risk financing methods, assessed the effectiveness of existing disaster insurance practices, and proposed strategies for improving disaster risk reduction (DRR). Literature review was used to analyse disaster fund and insurance implementation. A building vulnerability simulation, based on Federal Emergency Management Agency's (FEMA) P-154 rapid visual screening, determined the appropriate financing strategy. State buildings were assessed using nine vulnerability factors and categorised by seismicity. The research found that disaster financing mostly relied on national funds to cover all disaster damages. Existing disaster insurance lacked clarity in defining insurable buildings, resulting in broad inclusion. Vulnerability assessments showed that each building type exhibited different potential earthquake damage levels. Consequently, insurance coverage is recommended for high-damage categories but discouraged for low to moderately vulnerable buildings. This study offered insights into Indonesia's current disaster risk financing and insurance landscape, and provides a strategic framework for optimising these mechanisms to better protect state buildings from earthquake-related risks.